Analisis Kompetensi Pedagogik Guru (PAI) Di SD Negeri Lubuk Rumbai Kecamatan Rupit Kabupaten Musi Rawas Utara - Yuliansa, Erni; Fitriyani, Fitriyani; Mukmin, Taufik (Edification Journal : Pendidikan Agama Islam, 2024)
This thesis discusses the Pedagogical Competencies of Islamic Religious Education Teachers which relate to the moral and spiritual aspects of students. Students who still lack enthusiasm for learning are due to poor learning management and a lack of teaching staff. Therefore, the aim of this research is to find out what the pedagogical competence of PAI teachers at Lubuk Rumbai State Elementary School is and what efforts PAI teachers have made to improve pedagogical competence at Lubuk Rumbai State Elementary School. This type of research uses field research, with a qualitative approach. In collecting data, researchers used observation, interviews and documentation methods. This data was collected from various information found, results that were relevant to the problem under study were analyzed qualitatively through data collection, data reduction, data presentation and drawing conclusions. Elements in pedagogical competence have five roles, namely the ability to understand the character of students, the ability to create learning designs, develop a curriculum, the ability to carry out educational learning and the ability to evaluate learning outcomes. In improving the quality of learning, many efforts are made by teachers, one of which is taking part in lesson studies and seminars, mastering theory and learning, developing curriculum, following actual news from learning media. Keywords: Analysis, Pedagogical Competence, PAI Teacher